Numerical study of shock-turbulent boundary layer interactions with incipient and complete separation. (1st January 2011) - Agostini, Lionel; Dupont, Pierre; Larchevêque, Lionel; Dussauge, Jean Paul
This paper aims at describing the main features of a separated boundary layer in shock reflection at a Mach number of 2.3. The data used for this analysis were taken from large eddy simulations of the interactions for three-shock intensities, resulting in flow cases from incipient to fully separated. Computational results were validated versus experimental data. The main space-time properties of the reflected shock motion are described together with their link with the other flow regions. The analysis of the correlations between the shock motion and the unsteady pressure field provides information about the origins of shock unsteadiness.